The Effect of Giving Tamarind Turmeric Pudding on Menstrual Pain in Adolescent Women At State Madrasah Tsanawiyah (MTSN) 4 Kerinci - Neneng Fitria Ningsih; Desri Nova; Yovi Seftrianic; Yeltra Army; Devi Eka Safitri (General Multidisciplinary Research Journal, 2025)
Introduction: Overview: In 2023, 117,418 individuals (71.04%) in Indonesia would have dysmenorrhea, with 63,081 people (54.89%) having primary dysmenorrhea and 10,565 people (12.8%) having secondary dysmenorrhea. According to data reports from Jambi Province, 78.1% of adolescent females have menstrual pain throughout their periods, indicating that dysmenorrhea is an issue among teens in 2023. This study aims to determine how delivering tamarind turmeric pudding to young women at State Madrasah Tsanawiyah (MTsN) 4 Kerinci in 2024 affects their menstrual pain. Methods: This study uses a pretest-posttest one-group design and is pre-experimental. It was conducted in September and October 2024 at State Madrasah Tsanawiyah (MTsN) Negeri 4 Kerinci. Results: This kind of study uses a pretest-posttest one-group design and is pre-experimental. This study was conducted at Madrasah Tsanawiyah (MTs) Negeri 4 Kerinci in 2024 during September and October. With a sample size of 18, the study's population consisted of all 85 young women who attended Madrasah Tsanawiyah (MTs) Negeri 4 Kerinci in 2024. method of purposeful sampling. A numerical rating scale observation sheet was used to gather the data for this study. The t-test, specifically the paired t-test, was used for both univariate and bivariate analysis. According to the study, young women's average menstrual discomfort was 5.25 with a standard deviation of 0.775 before receiving tamarind turmeric pudding, and 2.69 following. Conclusion and Suggestion: that menstruation pain is lessened by sour tamarind turmeric pudding. It is advised that health professionals educate young women who suffer from menstrual discomfort about non-pharmacological treatments such using receiving tamarind turmeric pudding.